KEBIJAKAN KOMISI PENYIARAN INDONESIA TERHADAP KONTEN TELEVISI EDISI RAMADHAN - Najikh, Ahmad Hayyan; Ardy Zaini, Muhammad (Dakwah, 2020)
The research entitled " THE KPI POLICY IN THE TELEVISION INDUSTRY (Case Study of KPI Policy on Content of Television Broadcasting Program Ramadhan Edition)" is motivated by the lack of maximum role of the government in creating situations and conditions conducive to worship in the month of Ramadan, especially in the realm of television media broadcasting the Ramadan edition)". The concrete form is that some of the da'wah programs on television present more shows than guidance, some deviate to the point of lacking in everyday examples. Whereas television, if seen from the perspective of da'wah, can be said to be an effective da'wah media. And the role of government here is institutionally represented by KPI (Indonesian Broadcasting Commission). This study aims to find out exactly how the Indonesian Broadcasting Commission's policies towards television media content, especially during the month of Ramadan. Because of KPI's findings, found violations committed by television media are a repetition of previous years. This research is a qualitative study using policy analysis as a methodology for analyzing KPI policies, which includes collecting data from online news, the Broadcasting Law, KPI's official website and MUI statement, and then analyzing the findings. The results show that if theoretically, the policies issued by KPI institutions are legally strong and must be obeyed by all parties related to KPI institutions. But in reality there are still those who have not yet implemented it. And when related to the theories above, the factors that cause implementation to fail are due to factors such as the selection of the wrong strategy, or the wrong "machine" or "instrument"; "Programming" bureaucracy is wrong; the operation operation is bad; there is something wrong at the "executive level"; or a bad response to a problem. From these factors, it could be that the factors within the KPI are the poor level of implementing policies. The lack of strict sanctions provided, so that KPI institutions do not have the authority in the eyes of media stakeholders. And can also be bad bureaucratic instruments.